Response to name and its value for the early detection of developmental disorders: Insights from autism spectrum disorder, Rett syndrome, and fragile X syndrome. A perspectives paper - Zhang, D.; Roche, L.; Bartl-Pokorny, K.; Krieber, M.; McLay, L.; Bolte, Sven; Poustka, L.; Sigafoos, J.; Gugatschka, M.; Einspieler, C.; Marschik, P. (Pergamon Press, 2018)
Background: Responding to one's own name (RtN) has been reported as atypical in children with developmental disorders, yet comparative studies on RtN across syndromes are rare. Aims: We aim to (a) overview the literature on RtN in different developmental disorders during the first 24 months of life, and (b) report comparative data on RtN across syndromes. Methods and procedures: In Part 1, a literature search, focusing on RtN in children during the first 24 months of life with developmental disorders, identified 23 relevant studies. In Part 2, RtN was assessed utilizing retrospective video analysis for infants later diagnosed with ASD, RTT, or FXS, and typically developing peers. Outcomes and results: Given a variety of methodologies and instruments applied to assess RtN, 21/23 studies identified RtN as atypical in infants with a developmental disorder. We observed four different developmental trajectories of RtN in ASD, RTT, PSV, and FXS from 9 to 24 months of age. Between-group differences became more distinctive with age. Conclusions and implications: RtN may be a potential parameter of interest in a comprehensive early detection model characterising age-specific neurofunctional biomarkers associated with specific disorders, and contribute to early identification.